Are fungicides a driver of European foulbrood disease in honey bee colonies pollinating blueberries? - Thebeau, Jenna M.; Cloet, Allyssa; Liebe, Dana; Masood, Fatima; Kozii, Ivanna V.; Klein, Colby D.; Zabrodski, Michael W.; Biganski, Sarah; Moshynskyy, Igor; Sobchishin, Larhonda; Wilson, Geoff; Guarna, Maria Marta; et al. (Frontiers in Ecology and Evolution, 2023)
Introduction Blueberry producers in Canada depend heavily on pollination services provided by honey bees (Apis mellifera L.). Anecdotal reports indicate an increased incidence of European foulbrood (EFB), a bacterial disease caused by Melissococcus plutonius, is compromising pollination services and colony health. Fungicidal products are commonly used in blueberry production to prevent fungal diseases such as anthracnose and botrytis fruit rot. Pesticide exposure has been implicated in honey bee immunosuppression; however, the effects of commercial fungicidal products, commonly used during blueberry pollination, on honey bee larval susceptibility to EFB have not been investigated. Methods Using an in vitro infection model of EFB, we infected first instar honey bee larvae with M. plutonius 2019 BC1, a strain isolated from an EFB outbreak in British Columbia, Canada, and chronically exposed larvae to environmentally relevant concentrations of fungicide products over 6 days. Survival was monitored until pupation or eclosion. Results We found that larvae chronically exposed to one, two, or three fungicidal products [Supra® Captan 80WDG (Captan), low concentration of Kenja™ 400SC (Kenja), Luna® Tranquility (Luna), and/or Switch® 62.5 WG (Switch)], did not significantly reduce survival from EFB relative to infected controls. When larvae were exposed to four fungicide products concurrently, we observed a significant 24.2% decrease in survival from M. plutonius infection (p = 0.0038). Similarly, higher concentrations of Kenja significantly reduced larval survival by 24.7–33.0% from EFB (p < 0.0001). Discussion These in vitro results suggest that fungicides may contribute to larval susceptibility and response to M. plutonius infections. Further testing of other pesticide combinations is warranted as well as continued surveillance of pesticide residues in blueberry-pollinating colonies.